Protective Immunity and Vaccination Against Cutaneous Leishmaniasis - Okwor, Ifeoma; Mou, Zhirong; Dong, Liu; UZONNA, JUDE E. (Frontiers in Immunology, 2012)
Although a great deal of knowledge has been gained from studies on the immunobiology of leishmaniasis, there is still no effective vaccine against the disease. This strongly suggests that we still do not understand the factors that control and/or regulate the development and sustenance of anti-Leishmania immunity, particularly those associated with secondary (memory) immunity. Such an understanding is critically important for designing effective vaccines against the disease. Here we review the literature on the correlate of protective anti-Leishmania immunity and vaccination strategies against leishmaniasis with a bias emphasis on experimental cutaneous leishmaniasis.